2008
DOI: 10.1007/s10494-008-9169-8
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Analysis for a Single Collapsing Bubble

Abstract: This work presents a sensitivity analysis for cavitation processes, studying in detail the effect of various model parameters on the bubble collapse. A complete model (Hauke et al. Phys Rev E 75:1-14, 2007) is used to obtain how different parameters influence the collapse in SBSL experiments, providing some clues on how to enhance the bubble implosion in real systems. The initial bubble radius, the frequency and the amplitude of the pressure wave are the most important parameters determining under which condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Even when vapor mass diffusion controls the overall collapse processes numerical studies have shown that the kinetics of phase change influence the dynamics of vapor bubbles [91] and the violence of the collapse generated [73]. Parametric studies based on a complete one-dimensional model accounting for mass transfer effects reveal that the dependency of the peak temperatures reached during the bubble collapse on the ambient temperature is directly linked to the mass transfer model [72], revealing the intricate mechanisms between the process of phase change and the collapse process of a gas/vapor bubble.…”
Section: Gas/vapor Bubblesmentioning
confidence: 99%
“…Even when vapor mass diffusion controls the overall collapse processes numerical studies have shown that the kinetics of phase change influence the dynamics of vapor bubbles [91] and the violence of the collapse generated [73]. Parametric studies based on a complete one-dimensional model accounting for mass transfer effects reveal that the dependency of the peak temperatures reached during the bubble collapse on the ambient temperature is directly linked to the mass transfer model [72], revealing the intricate mechanisms between the process of phase change and the collapse process of a gas/vapor bubble.…”
Section: Gas/vapor Bubblesmentioning
confidence: 99%